Compressibility characteristics of tropical peat using Rowe cell consolidation - Kolay, P.K; Sii, H.Y; Taib, S.N.L. (World Journal of Engineering, 2012)
This paper presents the results of the physical and compressibility characteristics of tropical peat, from Matang, Malaysia. Different physical properties tests have been conducted on peat samples. Rowe cell consolidation and standard 1-D consolidation tests were performed on undisturbed peat samples to evaluate the compressibility characteristics. A specially designed and fabricated peat sampler has been used to collect the undisturbed peat sample for Rowe cell consolidation test. The laboratory test results revealed that peat has a large void ratio with high water content and undergone large consolidation settlements when applied load. The results of Rowe cell test can be used to simulate close to the the field geotechnical characteristics of peat for any design or numerical modelling where reliable data is most important.